Engaging audiences with data visualization - Murray, Scott (O'Reilly Media, 2014)
"Edward Tufte, Stephen Few, and others espouse graphical purity and simplicity when visualizing data. Yet while "pure" visualizations may function successfully for experts, they are not necessarily useful for communicating meaning to lay audiences. Engaging non-expert audiences is essential to communicating the value of one's data and research. Fortunately, we can draw on principles and practices for engagement from the fields of graphic design, interaction design, and (data) journalism."--Resource description page.